2004
DOI: 10.7589/0090-3558-40.2.361
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Escherichia coli O157:H7 in White-tailed Deer from Louisiana

Abstract: Escherichia coli O157:H7 (EC O157) is an important zoonosis. White-tailed deer (Odocoileus virginianus) have been implicated in transmission of this bacterium to humans and have been suggested as reservoirs that might affect carriage in cattle populations. Our study objectives were to estimate prevalence of EC O157 in feces of hunter-harvested deer and to describe fecal shedding patterns in a captive herd sampled over 1 yr. Prevalence of EC O157 in hunter-harvested deer was 0.3% (nϭ338). In August 2001, EC O15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 10 publications
1
36
2
Order By: Relevance
“…The STEC frequency demonstrated here among wild ungulates (19.4% overall [22.3% in elk, 15.3% in deer]) is similar to the highest reported among dairy cattle (13) and is considerably higher than the frequency of O157:H7 reported among U.S. deer (7,9,24). Both sorbitol fermentative and nonfermentative E. coli were isolated in this study, and both produced detectable Stx toxin and/or presented detectable stx genes.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…The STEC frequency demonstrated here among wild ungulates (19.4% overall [22.3% in elk, 15.3% in deer]) is similar to the highest reported among dairy cattle (13) and is considerably higher than the frequency of O157:H7 reported among U.S. deer (7,9,24). Both sorbitol fermentative and nonfermentative E. coli were isolated in this study, and both produced detectable Stx toxin and/or presented detectable stx genes.…”
mentioning
confidence: 67%
“…STEC are transferred by the fecal-oral route, so wild animals and cattle sharing common areas would likely experience interspecies transfer (23). Although not studied extensively, O157:H7 isolates have been identified in wild deer (7,9,10,23,24) and have been implicated in at least one human infection (16,27).Nonetheless, wild deer are rarely screened for either Shiga toxin or its genes.Fecal pellets (collected from live mule deer and elk in Idaho from December 2005 to March 2006) cultured in tryptic soy broth (TSB) (Becton Dickinson, Franklin Lakes, NJ) at 37°C were screened for Shiga toxin (Remel ProSpecT Shiga toxin microplate ELISA kit; Remel, Inc., Lexena, KS) and the stx 1 , stx 2 , eae (intimin), and ehx (enterohemolysin, also known as hemolysin A [hlyA]) genes (25) from total DNA (isolated using the Puregene DNA purification system [Gentra, Minneapolis, MN]) via PCR (Table 1).Fecal cultures (n ϭ 160) screened in this manner yielded 31/160 (19.4%) positive for Shiga toxin or the stx 1 or stx 2 genes (Table 2). From this pool, 26/31 (83.9%) amplified either stx 1 or stx 2 genes but no toxin was detected, while 5/31 (16.1%) exhibited both stx genes and toxin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our data suggest that IEEs were acquired by O55:H7, typical O157:H7, atypical O157: H7, and LSU-61 independently and that these strains diverged earlier. Intriguingly, an O157:H7 strain similar to LSU-61 was isolated from a red deer in 2001 in Europe, but it has not yet been reported to cause human disease (38). This suggests that IEE was acquired separately by each serotype.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we detected the stx1 gene in 90 % of the tested faecal samples and in 50 % of the tested samples the stx2 gene was determined to be present, which is a considerably high percentage of detection frequency when compared to the Norwegian reindeer (Rangifer tarandus tarandus; Aschfalk et al 2003) or a white-tailed deer (Odocoileus virginianus) from Louisiana (Dunn et al 2004) and Pennsylvania (Kistler et al 2011). Lillehaug et al (2005 reported that no E. coli O157 isolates, both Shiga toxins producing as well as not Shiga toxins producing, were observed in four different wild cervid species: red deer (Cervus elaphus), roe deer (Capreolus capreolus), moose (Alces alces) and reindeer from the central Norway.…”
Section: Discussionmentioning
confidence: 92%